Solutions to social problems: lessons from state and local governments - Eitzen, David Stanley (Pearson/Allyn and Bacon, 2008)
Introduction: States and cities solving social problems -- Democracy and campaign reform -- The environment : initiatives to reduce global warming -- Building America's infrastructure -- Improving education -- Poverty, homelessness and affordable housing -- Improving wages for the poor and the near poor -- Health care for all